Delmar's basic nursing skills DVD-ROM [ - Altman, Gaylene Bouska; Altman, Gaylene Bouska; Morrison, Agnes M. (Thomson/Delmar Learning, 2004)
"Containing approximately 150 minutes of step-by-step video ... focusing on physical assessment, vital signs, bed making, personal care, restraints, infection/hygiene, bathing, ambulation/activity"--Container.